Effects Of Breastfeeding Techniques On Sore Nipples In Postpartum Mothers At Siti Fatimah Hospital Makassar - Andi Rizky Amaliah; Suarni; Sriwulan Ndari (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2023)
Nipple blisters often occur in breastfeeding mothers due to incorrect breastfeeding techniques. So far, sore nipples dominate the complication in the lactation process, which is caused by a lack of information regarding the breastfeeding process. Data showed that mothers who experience sore nipples worldwidewere 56.4%, while in Indonesia by 79.3%. Data in Sitti Fatimah hospital depicts that 14.8% mothers experienced sore nipples in 2021. This study aimed to recognize the effects of breastfeeding techniques on sore nipples in postpartum mothers.This was quasi experimental study with a treatment group without a control group. The number of samples was 16 respondents of population by 85 mothers selected by purposive sampling. Data collection applied questionnaires and observation sheets. The results revealed that there was a significant change in the value of degree of sore nipples before and after the correct breastfeeding technique intervention was applied. Paired Sample Test obtained p-value = 0.000 (<0.05). It concluded that breastfeeding techniques influenced the sore nipples in postpartum mothers at Siti Fatimah Hospital. It is encouraged to postpartum mothers, especially primiparous ones to increase knowledge and insight on breastfeeding and the correct techniques, and for further researchers it is suggested to develop research related to health services that are carried out to increase knowledge of postpartum mothers, especially in primiparous.